Effect of Various Chemicals on Short Sequence Deinking of Waste Paper and its Pilot Plant Trials - Srivastava, Anita; Dhoundiyal, S. N.; Bhandari, K. S. (Indian Forester, 1999)
Short Sequence Deinking (SSD) of office waste, computer waste, magazines and newsprints was carried out using different doses of NaOH, Na2CO3 and detergent followed by their bleaching. 2% hypochlorite was used for office and computer waste deinked pulps while deinked pulps from magazines and newsprints were bleached with 1.2% H2O2. Strength and optical properties of both the pulps were adequate for newsprint production however, these were comparatively better for pulp produced using Na2CO3 as deinking chemical at laboratory scale. Pilot plant trials using sodium hydroxide (1.5%) and sodium silicate (3.0%) as deinking chemicals was carried out at 70°C temperature and 8% consistency in hydrapulper for one hour. Magnesium sulphate (0.50%), chelating agent (0.25%) and hydrogen peroxide (1.0%) were added to pulps and bleached for one hour for further brightening of pulps. Deinked and bleached pulp yield was 85.87% for old mixed waste papers and 79.79% for old magazines and periodicals. Paper possessing adequate strength properties; burst index, 2.51 ± 0.38; tensile 29.85 ± 2.31 and 20.81 ± 2.60 in machine and cross direction and tear index, 1.65 ± 0.31 and 1.95 ± 0.50 in machine and cross directions, respectively, was made on pilot plant. Brightness of deinked and bleached pulp was 70.30 ± 7.25. Strength properties and brightness were higher for pulp produced from magazines and periodicals as compared old mixed papers. Similar was the trend for strength properties and brightness of papers after aging. Runnability of papers on paper machine was satisfactory, in both the cases. Deinking conditions and paper making parameters on pilot plant are discussed in the paper.